Multivariate analysis and character association studies for yield and nutritional characters in swarna and type 3 RIL population of rice (Oryza sativa L.) - Shivani, Darmagaru; Neeraja, Cheruvuri Naga; Cheralu, Chandragiri; Shankar, Vuppu Gouri (Journal of Cereal Research, 2021)
The investigation was carried out in one hundred Swarna X Type 3RIL population of rice to understand the association among yield,yield attributing and nutritional traits. Their direct and indirecteffects on the grain yield using correlation and path analysis and theprincipal component analysis was assessed using multivariate analysis.Significant differences were observed among the RIL population forthe traits studied. High values of heritability and genetic advancewere observed for plant height, panicle weight, number of filled grainsper panicle, panicle weight, 1000-seed weight, grain yield per plant,grain iron and zinc concentration. Character association for the yieldattributing traits at both genotypic and phenotypic level revealedsignificant positive association of grain yield per plant with test weightand plant height. Path coefficient analysis revealed that test weighthad highest direct positive effect on grain yield per plant followedby plant height and filled grains per panicle. PCA showed that acumulative variance of 32.5% from PC1 attributed by grain iron, grainzinc, plant height and test weight would be beneficial in contributingto the total morphological diversity. RILs P45 and P57 have shownhigher grain yield per plant with high iron and zinc concentrations.Thus, the trait test weight that showed positive and direct associationwith grain yield can be focused in selection and can be utilized forimprovement in future breeding programmes.